Environmental Charities and Their Work - Joanna Brundle (India Booktale, 2018)
This factual series has been developed with direct input from some of the world's major charities to introduce readers to charity, giving and fundraising. We take a look why charities exist, who and what they support, and how they raise money, and we give young activists ideas on how to get involved and support their favorite charities. This interesting series helps young readers engage with the wider world and consider far-reaching topics from a charitable perspective.
Keywords: SDG 17: Partnerships For The Goals; Global Issues -- Global Issues; Environment Issues -- Environment Issues